Nitensidine A, a guanidine alkaloid from Pterogyne nitens, is a novel substrate for human ABC transporter ABCB1 - Tajima, Yasuhiro; Nakagawa, Hiroshi; Tamura, Ai; Kadioglu, Onat; Satake, Kazuhiro; Mitani, Yuji; Murase, Hayato; Regasini, Luis Octavio; Silva Bolzani, Vanderlan; Ishikawa, Toshihisa; Fricker, Gert; Efferth, Thomas (Phytomedicine, 2014)
The Pterogyne nitens (Fabaceae) tree, native to South America, has been found to produce guanidine alkaloids as well as bioactive flavonols such as kaempferol, quercetin, and rutin. In the present study, we examined the possibility of interaction between human ATP-binding cassette (ABC) transporter ABCB1 and four guanidine alkaloids isolated from P. nitens (i.e., galegine, nitensidine A, pterogynidine, and pterogynine) using human T cell lymphoblast-like leukemia cell line CCRF-CEM and its multi-drug resistant (MDR) counterpart CEM/ADR5000. In XTT assays, CEM/ADR5000 cells were resistant to the four guanidine alkaloids compared to CCRF-CEM cells, although the four guanidine alkaloids exhibited some level of cytotoxicity against both CCRF-CEM and CEM/ADR5000 cells. In ATPase assays, three of the four guanidine alkaloids were found to stimulate the ATPase activity of ABCB1. Notably, nitensidine A was clearly found to stimulate the ATPase activity of ABCB1 as strongly as the control drug, verapamil. Furthermore, the cytotoxic effect of nitensidine A on CEM/ADR5000 cells was synergistically enhanced by verapamil. Nitensidine A inhibited the extrusion of calcein by ABCB1. In the present study, the possibility of interaction between ABCB1 and two synthetic nitensidine A analogs (nitensidine AT and AU) were examined to gain insight into the mechanism by which nitensidine A stimulates the ATPase activity of ABCB1. The ABCB1-dependent ATPase activity stimulated by nitensidine A was greatly reduced by substituting sulfur (S) or oxygen (O) for the imino nitrogen atom (N) in nitensidine A. Molecular docking studies on human ABCB1 showed that, guanidine alkaloids from P. nitens dock to the same binding pocket as verapamil. Nitensidine A and its analogs exhibit similar binding energies to verapamil. Taken together, this research clearly indicates that nitensidine A is a novel substrate for ABCB1. The present results also suggest that the number, binding site, and polymerization degree of the isoprenyl moiety in the guanidine alkaloids and the imino nitrogen atom cooperatively contribute to their stimulation of ABCB1's ATPase activity.